Moringa oleifera ameliorates age-related memory decline and increases endogenous antioxidant response in Drosophila melanogaster exposed to stress (African Journal of Biomedical Research, 2020)
Age-related dementia has been estimated to double every 20 years. Despite the nutritional value of Moringa oleifera Lam., its effect on age-related memory decline and its anti-ageing bioactive fractions are yet to be fully elucidated. In the present study, the crude methanol leaves extract of Moringa oleifera Lam. (MEMO) and its different fractions were screened for anti-ageing bioactivity in the fruit fly, Drosophila melanogaster w1118 whiteflies. A day-old virgin flies were reared in food supplemented with different concentrations of the methanol leaves extract of Moringa oleifera at 1, 2, and 5mg/ml respectively. A sequential bioassay-guided fractionation approach was subsequently adopted. Treated flies were subjected to lifespan, reproductive performance, climbing, memory and oxidative stress resistance assays according to established protocols. There was a dose-dependent effect of the leaves extract on lifespan, reproductive performance, climbing activity and oxidative stress resistance as age progressed (P < 0.05). Mean survival times of treated male and female flies increased by 12.3±1.2, 15.5±1.0 and 26.6±0.4%, and 12.0±1.1, 17.5±0.8 and 24.3±0.8% respectively, relative to the control. There was a significant increase in memory scores of the 50-day old aged flies in the 5mg/ml group P < 0.0001. The Moringa Ethyl acetate (EA) fraction F2 gave the highest anti-ageing bioactivity in the flies (P < 0.05). The leaves extract showed an ameliorative effect on age-related memory decline and an increase in oxidative stress resistance in Drosophila melanogaster w1118 whiteflies without the commonly found adverse effect in reproductive performance.